ALMA spectral survey of Supernova 1987A – molecular inventory, chemistry, dynamics and explosive nucleosynthesis. Issue 3 (5th April 2017) - Matsuura, M.; Indebetouw, R.; Woosley, S.; Bujarrabal, V.; Abellán, F. J.; McCray, R.; Kamenetzky, J.; Fransson, C.; Barlow, M. J.; Gomez, H. L.; Cigan, P.; De Looze, I; et al.
Abstract: We report the first molecular line survey of Supernova 1987A in the millimetre wavelength range. In the Atacama Large Millimeter/submillimeter Array (ALMA) 210–300 and 340–360 GHz spectra, we detected cold (20–170 K) CO, 28 SiO, HCO + and SO, with weaker lines of 29 SiO from ejecta. This is the first identification of HCO + and SO in a young supernova remnant. We find a dip in the J = 6–5 and 5–4 SiO line profiles, suggesting that the ejecta morphology is likely elongated. The difference of the CO and SiO line profiles is consistent with hydrodynamic simulations, which show that Rayleigh–Taylor instabilities cause mixing of gas, with heavier elements much more disturbed, making more elongated structure. We obtained isotopologue ratios of 28 SiO/ 29 SiO > 13, 28 SiO/ 30 SiO > 14 and 12 CO/ 13 CO > 21, with the most likely limits of 28 SiO/ 29 SiO >128, 28 SiO/ 30 SiO >189. Low 29 Si and 30 Si abundances in SN 1987A are consistent with nucleosynthesis models that show inefficient formation of neutron-rich isotopes in a low-metallicity environment, such as the Large Magellanic Cloud. The deduced large mass of HCO + (∼5 × 10 −6 M⊙ ) and small SiS mass (<6 × 10 −5 M⊙ ) might be explained by some mixing of elements immediately after the explosion. The mixing might have caused some hydrogen from the envelope to sink into carbon- and oxygen-rich zones after the explosion, enabling the formation of a substantial mass of HCO + . Oxygen atoms may have penetrated into silicon and sulphur zones, suppressing formation of SiS. Our ALMA observations open up a new window to investigate chemistry, dynamics and explosive nucleosynthesis in supernovae.